2009
DOI: 10.1007/s10620-009-0982-2
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Treatment of Patients with Recurrent Hepatitis C After Liver Transplantation with Pegylated Interferon

Abstract: The outcome of antiviral combination therapy for HCV reinfection after OLT can be best predicted by week-24 virologic response. The high SVR rates in patients with detectable HCV RNA at week 12 might suggest a prolonged treatment protocol in liver transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Additionally, the post‐LT recurrence of HCV infections is one of the major causes of morbidity and allograft loss after LT 11,14–16. Because the outcomes of post‐LT therapy with the classic antiviral agents PEG‐IFN and RBV are at most moderate with respect to a sustained virological response (SVR), LT patients constitute one of the classic difficult‐to‐treat groups 16–22. Newly introduced protease inhibitor (PI)–based triple therapy now offers promising perspectives for the management of LT patients, although TVR is not yet approved for use in LT patients.…”
mentioning
confidence: 99%
“…Additionally, the post‐LT recurrence of HCV infections is one of the major causes of morbidity and allograft loss after LT 11,14–16. Because the outcomes of post‐LT therapy with the classic antiviral agents PEG‐IFN and RBV are at most moderate with respect to a sustained virological response (SVR), LT patients constitute one of the classic difficult‐to‐treat groups 16–22. Newly introduced protease inhibitor (PI)–based triple therapy now offers promising perspectives for the management of LT patients, although TVR is not yet approved for use in LT patients.…”
mentioning
confidence: 99%
“…A sustained virological response (SVR; ie, the patient is serum‐negative for HCV by polymerase chain reaction 6 months after the cessation of therapy) occurs in approximately 40% to 50% of patients with genotype 1 and in 80% of patients with genotype 2 or 3 9‐12. After LT, such therapy is associated with frequent adverse events, and response rates, varying between 30% and 40%, are substantially lower in all HCV‐positive patients 13‐15…”
mentioning
confidence: 99%
“…Non-1 genotype [26, 27, 199, 202, 213, 218, 220, 234, 235], absence of prior antiviral therapy [194], early virologic response (evaluated after 3 months) [27, 28, 202, 205, 207210, 214, 215, 217221, 223, 235], rapid virologic response (evaluated after 1 month) [206, 208, 220], adherence to therapy [27, 202, 207, 211, 213, 216218], low baseline viral load [27, 208, 211213, 216, 221, 222], low pretreatment fibrosis stage [26, 28, 204], younger donor age [26, 28, 221, 234], polymorphisms close to the IL-28B gene [6669], and cyclosporine-based immunosuppression [26, 234, 236] are associated with an improved SVR. Most studies demonstrated improved biochemical and histologic findings, even in virologic nonresponders [222, 237], but whether antiviral therapy slows disease progression in nonresponders has not yet been demonstrated.…”
Section: Antiviral Treatmentmentioning
confidence: 99%